The host dark matter haloes of [O II] emitters at 0.5 < z < 1.5. Issue 3 (30th October 2017) - Gonzalez-Perez, V; Comparat, J; Norberg, P; Baugh, C M; Contreras, S; Lacey, C; McCullagh, N; Orsi, A; Helly, J; Humphries, J
Abstract: Emission line galaxies (ELGs) are used in several ongoing and upcoming surveys (SDSS-IV/eBOSS, DESI) as tracers of the dark matter distribution. Using a new galaxy formation model, we explore the characteristics of $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters, which dominate optical ELG selections at z ≃ 1. Model $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters at 0.5 <  z  < 1.5 are selected to mimic the DEEP2, VVDS, eBOSS and DESI surveys. The luminosity functions of model $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters are in reasonable agreement with observations. The selected $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters are hosted by haloes with M halo ≥ 10 10.3 h −1 M⊙, with ∼90 per cent of them being central star-forming galaxies. The predicted mean halo occupation distributions of $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters have a shape typical of that inferred for star-forming galaxies, with the contribution from central galaxies, $\langle N \rangle _{{\rm \left[O\, {\rm \scriptscriptstyle II}\right]\, cen}}$, being far from the canonical step function. The $\langle N \rangle _{{\rm \left[O\, {\rm \scriptscriptstyle II}\right]\, cen}}$ can be described as the sum of an asymmetric Gaussian for discs and a step function for spheroids, which plateau below unity. The model $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters have a clustering bias close to unity, which is below the expectations for eBOSS and DESI ELGs. At z  ∼ 1, a comparison with observed g -band-selected galaxy, which is expected to be dominated by $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters, indicates that our model produces too few $\left[{\rm O}\, {\rm \scriptstyle II}\right]$ emitters that are satellite galaxies. This suggests the need to revise our modelling of hot gas stripping in satellite galaxies.